OC-033 Initial experience of a nurse-led irritable bowel syndrome clinic. (17th June 2017) - Neilson, M; Caulfield, L; Morris, AJ; Gaya, D; Winter, J; Cahill, A; Lachlan, N; Stanley, AJ; Forrest, E; Gillespie, R; Barclay, S; Smith, LA
Abstract : Please see PTU-080A